1990
DOI: 10.1128/mcb.10.10.5160
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a protein altered in mutants resistant to microtubule inhibitors as a member of the major heat shock protein (hsp70) family.

Abstract: A major cellular protein (P2; -70 kilodaltons) which is altered in Chinese hamster ovary (CHO) cell mutants resistant to the microtubule inhibitors coichicine and podophyllotoxin has been shown to correspond to the constitutive form of the 70-kilodalton heat shock protein (hsc7O). The inference that P2 and hsc7O are the same protein is based on the following observations: (i) migration of P2 in two-dimensional polyacrylamide gels in the same position as that reported for hsc7O; (ii) cross-reactivity of a monoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…We wished to determine whether this association of tau with Hsp70͞90 occurs between free tau and chaperones or microtubule-associated tau and chaperones. We reasoned that it would be difficult to address this in cells by using immunofluorescence analysis because Hsp90͞70 are diffusely distributed in the cytosol; although it has been shown that Hsp70 also colocalizes with microtubules (34)(35)(36). Therefore we used a technique involving cell permeabilization and removal of cytosol leaving microtubules and some cytosolic constituents intact (Fig.…”
Section: Inverse Relationship Between Molecular Chaperones and Tau Inmentioning
confidence: 99%
“…We wished to determine whether this association of tau with Hsp70͞90 occurs between free tau and chaperones or microtubule-associated tau and chaperones. We reasoned that it would be difficult to address this in cells by using immunofluorescence analysis because Hsp90͞70 are diffusely distributed in the cytosol; although it has been shown that Hsp70 also colocalizes with microtubules (34)(35)(36). Therefore we used a technique involving cell permeabilization and removal of cytosol leaving microtubules and some cytosolic constituents intact (Fig.…”
Section: Inverse Relationship Between Molecular Chaperones and Tau Inmentioning
confidence: 99%
“…Hsc70 associates with both intact MTs (15)(16)(17)(18)(19) and tubulin directly through its nucleotidebinding domain (NBD), suggesting functional regulation of tubulin by Hsc70 beyond proteostasis (20). Hsc70 also interacts with the microtubule (MT)-associated protein (MAP) tau, a putative 'typical' client of Hsc70 (6,(21)(22)(23) further suggesting that Hsc70 uniquely regulates MT dynamics (24,25). In addition to its role in MT stability, abnormal tau accumulation is linked to the pathology of a number of neurodegenerative diseases including Alzheimer's disease (AD), frontotemporal dementia (FTD), Pick's disease and chronic traumatic encephalopathy (26).…”
Section: Introductionmentioning
confidence: 99%
“…Although the synthesis of HSP70 is greatly enhanced by various physiological stressors, it also constitutes a major protein under normal growth conditions and has been shown to be essential for cellular growth. Gene cloning and sequencing studies on HSP70 show that the primary structure of this protein has been highly conserved during evolution in species ranging from bacteria to plants to humans (27,34).In recent years, although HSP70 homologs have been cloned from numerous bacterial and eukaryotic species (1,2,4,6,12,14,18,21,32,37,38,41,42) …”
mentioning
confidence: 99%
“…In recent years, although HSP70 homologs have been cloned from numerous bacterial and eukaryotic species (1,2,4,6,12,14,18,21,32,37,38,41,42) …”
mentioning
confidence: 99%